2022
DOI: 10.3390/rs14205208
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Spatiotemporal Pattern of Sandy Island Ecosystem Health during the Last Decades Based on Remote Sensing

Abstract: Sandy islands suffer multiple external disturbances and thus experience drastic temporal ecological changes, and the two parts, that is, the states of essential components (Part 1) and the resilience under multiple disturbances (Part 2), are both indispensable to the sandy island ecosystem health. In this study, a model for the sandy island ecosystem health was established by integrating the two parts. In Part 1, the states were measured following the framework of vegetation, soil, and landscape, and a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Duan et al [18] utilized high-resolution temporal continuous MODIS remote sensing data to focus on the dynamic changes in Horqin Sandy Land from 2000 to 2015. Various studies have demonstrated that the remote sensing index serves as an important indicator for monitoring dynamic changes in sandy lands through remote sensing [6,12,13,16,[19][20][21][22][23][24][25][26][27], and remote sensing data monitoring methods have become the primary approach for monitoring the characteristics of sandy land changes. However, owing to the influence of NDVI changes on the FVC, which is affected by meteorological conditions, there may be some randomness in the dynamic characteristics of sand changes during isolated years (such as a sudden increase in precipitation in the sand area that year, leading to a contraction in the area of sand monitored by the FVC).…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al [18] utilized high-resolution temporal continuous MODIS remote sensing data to focus on the dynamic changes in Horqin Sandy Land from 2000 to 2015. Various studies have demonstrated that the remote sensing index serves as an important indicator for monitoring dynamic changes in sandy lands through remote sensing [6,12,13,16,[19][20][21][22][23][24][25][26][27], and remote sensing data monitoring methods have become the primary approach for monitoring the characteristics of sandy land changes. However, owing to the influence of NDVI changes on the FVC, which is affected by meteorological conditions, there may be some randomness in the dynamic characteristics of sand changes during isolated years (such as a sudden increase in precipitation in the sand area that year, leading to a contraction in the area of sand monitored by the FVC).…”
Section: Introductionmentioning
confidence: 99%